Monsoonal and lunar variability in microzooplankton abundance and community structure in the Terusan mangrove creek (Malaysia) - Yong, Y.L.; Chew, L.L.; Lee, C.W.; Chong, V.C. (Taylor & Francis, 2016)
ABSTRACT: This study documents the monsoonal and lunar effects on species composition and abundance of microzooplankton in a tropical estuary. We investigated microzooplankton abundance in relation to the various environmental and biotic parameters, sampled in the Matang mangrove (Malaysia) from April 2013 to February 2014. A total of 39 microzooplankton taxa comprising four major groups, i.e. loricate ciliates (37.72%), aloricate ciliates (29.46%), dinoflagellates (24.33%) and meroplanktonic nauplii (8.49%) were identified. The loricate ciliates were the most diverse group with 31 taxa recorded. Four major species of loricate ciliates were identified, i.e. Tintinnopsis beroidea, Tintinnopsis rotundata, Stenosemella avellana and Tintinnidium primitivum, while Strombidiidae and Strobilidiidae dominated the aloricate ciliates. Although small loricate ciliates were ubiquitous, redundancy analysis shows marked shifts in microzooplankton community structure, from one that was dominated by loricate ciliates during the drier SW monsoon, to aloricate ciliates at the onset of the wet NE monsoon, and then to dinoflagellates towards the end of the drier NE monsoon period. These shifts were associated with rainfall, dissolved inorganic nutrients, salinity, temperature and microbial food abundance. There was no clear lunar effect on abundance of microzooplankton except for Favella ehrenbergii and copepod nauplii, which were more abundant during neap than spring tides.